In my time of dying [compact disc, unabridged] : how I came face-to-face with the idea of an afterlife - Junger, Sebastian (Simon & Schuster Audio, 2024)
For years as an award-winning war reporter, Sebastian Junger traveled to many front lines and frequently put his life at risk. And yet the closest he ever came to death was the summer of 2020 while spending a quiet afternoon at the New England home he shared with his wife and two young children. Crippled by abdominal pain, Junger was rushed to the hospital by ambulance. Once there, he began slipping away. As blackness encroached, he was visited by his dead father, inviting Junger to join him. "It's okay," his father said. "There's nothing to be scared of. I'll take care of you." That was the last thing Junger remembered until he came to the next day when he was told he had suffered a ruptured aneurysm that he should not have survived. This experience spurred Junger, a confirmed atheist raised by his physicist father to respect the empirical, to undertake a scientific, philosophical, and deeply personal examination of mortality and what happens after we die. How do we begin to process the brutal fact that any of us might perish unexpectedly on what begins as an ordinary day? How do we grapple with phenomena that science may be unable to explain? And what happens to a person, emotionally and spiritually, when forced to reckon with such existential questions?